Reimagining Secularism for Indonesia: Contextual Approaches Based on Madjid, Bhargava, Thiemann, and Taylor - Mustafa Kamil Thahir (Green Publisher Indonesia, 2025)
This article explores the feasibility of implementing a contextual form of secularism in Indonesia by synthesizing the ideas of four major thinkers: Nurcholish Madjid, Rajeev Bhargava, Ronald Thiemann, and Charles Taylor. It argues that secularism, particularly in religiously plural societies like Indonesia, should not be understood as the exclusion of religion from the public sphere. Rather, it should be reframed as a political and ethical framework that promotes justice, inclusivity, and democratic coexistence among diverse religious communities. By employing a qualitative-comparative methodology, this paper introduces the concept of “Contextual-Inclusive Secularism” as a normative model that aligns with Indonesia’s socio-religious realities. The article also outlines strategic pathways to foster support for this model among key stakeholders, including the government, academic institutions, religious organizations, and civil society. It concludes that the realization of such a model is attainable within a 15–25 year timeframe, provided that sustained interdisciplinary and collaborative efforts are undertaken across sectors.